The expanded clinical spectrum of anti-GABABR encephalitis and added value of KCTD16 autoantibodies - van Coevorden-Hameete, Marleen H; de Bruijn, Marienke A A M; de Graaff, Esther; Bastiaansen, Danielle A E M; Schreurs, Marco W J; Demmers, Jeroen A A; Ramberger, Melanie; Hulsenboom, Esther S P; Nagtzaam, Mariska M P; Boukhrissi, Sanae; Veldink, Jan H; Verschuuren, Jan J G M; et al. (Brain (London, England : 1878), 2019)
In this study we report the clinical features of 32 patients with gamma aminobutyric acid B receptor (GABABR) antibodies, identify additional autoantibodies in patients with anti-GABABR encephalitis that mark the presence of an underlying small cell lung carcinoma and optimize laboratory methods for the detection of GABABR antibodies. Patients (n = 3225) were tested for the presence of GABABR antibodies using cell-based assay, immunohistochemistry and live hippocampal neurons. Clinical data were obtained retrospectively. Potassium channel tetramerization domain-containing (KCTD)16 antibodies were identified by immunoprecipitation, mass spectrometry analysis and cell-based assays. KCTD16 antibodies were identified in 23/32 patients with anti-GABABR encephalitis, and in 1/26 patients with small cell lung carcinoma and Hu antibodies, but not in 329 healthy subjects and disease controls. Of the anti-GABABR encephalitis patients that were screened sufficiently, 18/19 (95%) patients with KCTD16 antibodies had a tumour versus 3/9 (33%) anti-GABABR encephalitis patients without KCTD16 antibodies (P = 0.001). In most cases this was a small cell lung carcinoma. Patients had cognitive or behavioural changes (97%) and prominent seizures (90%). Thirteen patients developed a refractory status epilepticus with intensive care unit admittance (42%). Strikingly, 4/32 patients had a rapidly progressive dementia. The addition of KCTD16 to the GABABR cell-based assay improved sensitivity of the in-house fixed cell-based assay, without loss of specificity. Twenty-two of 26 patients improved (partially) to immunotherapy or chemotherapy. Anti-GABABR encephalitis is a limbic encephalitis with prominent, severe seizures, but patients can also present with rapidly progressive dementia. The co-occurrence of KCTD16 antibodies points towards a paraneoplastic origin. The addition of KCTD16 improves the sensitivity of the cell-based assay.